THE EVOLUTION OF CUSTOMER EXPERIENCE (CX) CONSTRUCT: AN INTEGRATIVE CONCEPTUAL FRAMEWORK - Rahayu Syahputri; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
Customer Experience (CX) has emerged as a critical construct in contemporary marketing and management due to increasing competition and rising customer expectations. Traditionally, firms focused on service quality and customer satisfaction; however, the growing complexity of customer interactions has shifted attention toward holistic and multidimensional experiences. Despite its importance, the CX construct remains fragmented, with diverse definitions, dimensions, and theoretical perspectives across disciplines. This lack of integration creates challenges for both researchers and practitioners in understanding and managing CX effectively. To address this gap, this study adopts a qualitative approach using a systematic literature review to examine the evolution of CX and synthesize existing knowledge into a unified conceptual framework. The findings reveal that CX has evolved through transactional, relational, experiential, and digital phases, reflecting broader changes in business environments. The study identifies four key dimensions—functional, emotional, social, and digital—that interact dynamically across the customer journey to influence outcomes such as satisfaction, loyalty, and advocacy. The proposed integrative framework consolidates these dimensions into a cohesive model, addressing fragmentation in the literature and extending existing theories by incorporating digital and omnichannel perspectives. The study concludes that CX is a dynamic, multidimensional construct requiring a holistic management approach. It recommends future empirical validation and highlights the importance of leveraging emerging technologies to enhance customer experience in an increasingly experience-driven economy.